The Effect of Compensation and Workload on Turnover Intention among Generation Z Employees in Jakarta City - Chaesa Maheswara; Didin Kristinawati (Politeknik Siber Cerdika Internasional, 2026)
Background: The high turnover rate among Generation Z employees poses a major challenge for companies because it affects recruitment, training, and performance costs. In Jakarta, this phenomenon is often associated with dissatisfaction with compensation and workload pressure. Objective: This study aims to describe the conditions of compensation, workload, and turnover intention among Generation Z employees in Jakarta, as well as to analyze the impact of compensation and workload on turnover intention. Methods: This study was conducted with 150 respondents using a cross-sectional quantitative approach, a Likert-scale questionnaire, and purposive sampling. The data were analyzed using descriptive statistics and partial least squares structural equation modeling (PLS-SEM) to verify causal relationships. Results: Compensation and workload simultaneously had a significant positive effect on turnover intention, with R² = 0.878. Compensation was more dominant than workload, as indicated by its higher effect size (F² = 0.222) compared with workload (F² = 0.127). Workload and compensation each had a significant partial effect on turnover intention (t > 1.96; p < 0.05). The high R² value (0.878) is contextually justified, considering that both predictors are central structural determinants of turnover behavior among Generation Z employees, who are sensitive to compensation conditions and workload demands in the Jakarta labor market. The positive direction of the compensation effect (β = +0.540) reflects the reward–aspiration gap, in which higher compensation may increase market expectations and perceived professional recognition, thereby sustaining rather than suppressing exit intentions. Conclusion: Retention strategies for Generation Z employees should focus on improving fair and transparent compensation systems and ensuring proportionate workload management. The practical implications include evaluating compensation structures, task allocation, and working-time management to reduce employees’ intention to leave.